The effect of visual and verbal information during second-trimester ultrasound on state anxiety in pregnant women: a single-blind randomized controlled trial - Koc, Ozlem; Sonmez, Tugce; Oglak, Suleyman Cemil; Akcabay, Cigdem; Kavak, Salih Burcin (Bmc, 2025)
Introduction Pregnancy is a period often accompanied by anxiety due to physiological changes, uncertainties, and concerns about fetal health.To determine whether providing visual and verbal information during second-trimester detailed ultrasound (US) affects the state anxiety levels of pregnant women. Methods This randomized controlled trial was conducted between August and December 2023 and included 96 pregnant women who presented for detailed US at a university hospital in T & uuml;rkiye. Participants were randomly assigned using a simple randomization method (random number generator) into an intervention group (n = 51), who received real-time visual and verbal information during the US, and a control group (n = 45), who received no information during the scan. Spielberger's State-Trait Anxiety Inventory (STAI) was administered pre-and post-procedure. Data were analyzed using the SPSS 25.0 program with independent and paired sample t-tests and chisquare tests, with the significance level set at p < 0.05. Results Pre-test STAI-State scores were similar between groups (intervention: 36.41 +/- 9.8, control: 37.58 +/- 10.9; p = 0.584). Post-test scores significantly decreased in the intervention group (29.9 +/- 9.8; p < 0.001) and increased in the control group (43.9 +/- 10.7; p <0.001).The difference in post-test scores between groups was also statistically significant (p < 0.001).Trait anxiety scores were not significantly different between groups (p = 0.841), confirming baseline comparability. Conclusions Visual and verbal information provided during detailed US significantly reduces pregnant women's state anxiety levels. Integrating structured, reassuring communication into US examinations may enhance maternal psychological well-being during prenatal care.
Keywords: Pregnancy; Ultrasound; Maternal anxiety; Visual information; Prenatal care